Exploring Pre-Service Teachers’ Intercultural Communicative Competence and Global Citizen Learning in a Blended Intensive Program - POP, Raluca; MARC, Anamaria (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2026)
This paper aims to expand knowledge on undergraduate students’ development of intercultural communicative competence by examining the global citizen learning mindset facilitated by Erasmus Blended Intensive Programs (BIP). The mobility experience aligns with the internationalization of educational practices, enabling undergraduate students to develop global citizenship and thereby enhance their employability. A survey was used as the main research instrument. The study included 17 participants, and the data collected were analyzed both qualitatively and quantitatively through descriptive statistics offered by Google Forms' built-in tools and content analysis. The findings are similar to those of previous research, indicating the usefulness of participating in projects that provide relevant learning contexts and hands-on experiences, which contribute to the professional development of pre-service teachers.